2014
DOI: 10.1038/ncomms5576
|View full text |Cite
|
Sign up to set email alerts
|

Edge and confinement effects allow in situ measurement of size and thickness of liquid-exfoliated nanosheets

Abstract: Two-dimensional nanomaterials such as MoS 2 are of great interest both because of their novel physical properties and their applications potential. Liquid exfoliation, an important production method, is limited by our inability to quickly and easily measure nanosheet size, thickness or concentration. Here we demonstrate a method to simultaneously determine mean values of these properties from an optical extinction spectrum measured on a liquid dispersion of MoS 2 nanosheets. The concentration measurement is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
778
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 466 publications
(872 citation statements)
references
References 56 publications
72
778
3
1
Order By: Relevance
“…Statistical analysis of the TEM images showed the lateral nanosheet size to vary from ~100 to ~800 nm with a mean of 332 nm. Measurements of the optical absorbance spectrum (not shown) of the dispersion allowed us to use published metrics 44 to estimate the mean nanosheet length to be ~350 nm, in good agreement with TEM, and a mean nanosheet thickness of ~18 monolayers.…”
Section: Mos2-only Anodesmentioning
confidence: 79%
“…Statistical analysis of the TEM images showed the lateral nanosheet size to vary from ~100 to ~800 nm with a mean of 332 nm. Measurements of the optical absorbance spectrum (not shown) of the dispersion allowed us to use published metrics 44 to estimate the mean nanosheet length to be ~350 nm, in good agreement with TEM, and a mean nanosheet thickness of ~18 monolayers.…”
Section: Mos2-only Anodesmentioning
confidence: 79%
“…Previously, it has been demonstrated that for sonication-exfoliated nanosheets, the thickness appears to scale with nanosheet area. 29,32 This is unfortunate as it makes it difficult to produce large, yet thin, nanosheets. Shown in Fig.…”
Section: Blender Exfoliation Of Graphenementioning
confidence: 99%
“…To address this, we used the method rst described by Paton et al which calibrates the monolayer height using step height analysis. 26,29 Raman spectra were acquired on a Horiba Scientic LabRam HR aer drop casting 60 ml of the dispersion in total in 10 ml aliquots on preheated (150 C) Si/SiO 2 wafers (300 nm oxide). Areas showing thick deposits from the optical micrographs were chosen.…”
Section: Dispersion Preparation and Characterizationmentioning
confidence: 99%
“…Without the ability to achieve both these tasks, quantifying the geometrical effects is very difficult. However, recently, advances 31,48 in the processing and characterising of nanosheets produced by liquid phase exfoliation (LPE) has made both these tasks more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 However, one basic factor that has not been comprehensively or quantitatively explored is how the performance of nanosheet-containing electrodes depends on the geometry of the nanosheets within. Nanosheet size is known to strongly affect properties such as amphiphilicity 29 and optical behaviour 30,31 simply because of the relationships between sheet dimensions and parameters such as the fraction of edge atoms. As such, we expect nanosheet geometry to be a critical factor in all the applications described above.…”
Section: Introductionmentioning
confidence: 99%